Thermosensitive Hydrogel Mask Significantly Improves Skin Moisture and Skin Tone; Bilateral Clinical Trial - Quattrone, Anna; Czajka, Anna; Sibilla, Sara (Cosmetics (Basel), 2017)
Objective: A temperature-sensitive state-changing hydrogel mask was used in this study. Once it comes into contact with the skin and reaches the body temperature, it uniformly and quickly releases the active compounds, which possess moisturizing, anti-oxidant, anti-inflammatory and regenerative properties. Methods: An open label clinical trial was conducted to evaluate the effects of the test product on skin hydration, skin tone and skin ageing. Subjects applied the product to one side of their face and underwent Corneometer® and Chromameter measurements, Visual assessment of facial skin ageing and facial photography. All assessments and Self-Perception Questionnaires (SPQ) were performed at baseline, after the first application of the test product and after four applications. Results: After a single treatment we observed an increase in skin moisturisation, an improvement of skin tone/luminosity and a reduction in signs of ageing, all statistically significant. After four applications a further improvement in all measured parameters was recorded. These results were confirmed by the subjects’ own perceptions, as reported in the SPQ both after one and four applications. Conclusion: The hydrogel mask tested in this study is very effective in improving skin hydration, skin radiance and luminosity, in encouraging an even skin tone and in reducing skin pigmentation.